Utilizing Organic Fertilizers on Two Types of Soil to Improve Growth and Yield of Bawang Dayak (Eleutherine americana Merr) - Hastin Ernawati Nur Chusnul Chotimah; Adi Jaya; Hairu Suparto; Dewi Saraswati; Wardi Nawansyah (AGRIVITA, Journal of Agricultural Science, 2021)
Bawang dayak is a medicinal plant and can be grown as an economical crop with great potential value. Its contains secondary metabolites with biological activities that are important for human health. The main problem related with the production of bawang dayak is the standard of cultivation. The goal of the experiment was to study the effects of organic fertilizers and growing media on the growth and yield of bawang dayak. The polybag experiment was performed with two factors, namely soil type and organic fertilizer by Factorial Completely Randomized Design and located in the greenhouse of University of Palangka Raya. The treatments were chicken manure, oil palm empty-fruit-bunch compost (OPEFBC), and NASA granule as organic fertilizers, while Histosol and Ultisol served as growing media treatment. The results showed that OPEFBC gave the highest in Ultisol and chicken manure in Histosol to improve plant height. The highest number of tubers were developed in Ultisol. Chicken manure improved P and Fe bulbs tissue whereas the content of N and K bulbs grown in Ultisol was higher than those in Histosol.